2022
DOI: 10.3390/cancers14246062
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Mediated Activation of β-Catenin-TCF4-CEGRs/ALCDs Pathway Is an Essential Event in Development of Aggressive Hepatoblastoma

Abstract: Background and Aims: Hepatoblastoma (HBL), a deadly malignancy in children, is the most common type of pediatric liver cancer. We recently demonstrated that β-catenin, phosphorylated at S675 (ph-S675-β-catenin), causes pathological alterations in fibrolamellar hepatocellular carcinoma (FLC), by activating oncogenes and fibrotic genes via human genomic regions, known as cancer-enhancing genomic regions or aggressive liver cancer domains (CEGRs/ALCDs). The aim of this study was to determine the role of the ph-S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 30 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…Preceding studies have identified genomic regions of human DNA that promote oncogene expression in aggressive HBL. 7 8 9 10 11 12 Since the RELI algorithm identified ZBTB3 as a protein that frequently binds to CEGRs/ALCDs, 10 we searched the CEGRs/ALCDs and found a perfect binding site for ZBTB3 (Figure 1 A). ZBTB3 has previously been identified as an oncogene**** exhibiting oncogenic activity when it forms complexes with the chromatin remodeling protein SRCAP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preceding studies have identified genomic regions of human DNA that promote oncogene expression in aggressive HBL. 7 8 9 10 11 12 Since the RELI algorithm identified ZBTB3 as a protein that frequently binds to CEGRs/ALCDs, 10 we searched the CEGRs/ALCDs and found a perfect binding site for ZBTB3 (Figure 1 A). ZBTB3 has previously been identified as an oncogene**** exhibiting oncogenic activity when it forms complexes with the chromatin remodeling protein SRCAP.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies with a bigger number of patients are needed to understand if the higher increase of markers of neurons in lung metastases is a common feature of repetitive lung metastases. Because our group previously found that β-catenin phosphorylation at Ser675 was elevated in patients with HBL, 11 we examined the expression of ph-S675-β-catenin in HBL lung metastases. Western blot showed that ph-S675-β-catenin and total β-catenin were elevated in lung metastases (Figure 2 F, right).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations